The Relationship Between Mental Health Literacy and The Attitude Toward Seeking Professional Psychological Help in Junior High School - Rhifa Sasqi Nurazijah; Sifa Fauziah; Papat Patimah (Al-Hijrah Indonesia, 2026)
Adolescent mental health is an important aspect of individual development. However, a limited understanding of mental health causes adolescents to have difficulty recognizing psychological issues, which tends to result in attitudes that are less supportive when seeking professional help. This study aims to analyze the relationship between mental health literacy and attitudes toward seeking professional psychological help among adolescents at Bersemi Integrated Islamic Junior High School. This study used a quantitative approach with a cross- sectional design. The research sample consisted of 83 respondents selected through purposive sampling. Data collection was conducted using the Mental Health Literacy Questionnaire (MHLQ) and Attitudes Toward Seeking Professional Psychological Help (ATSPPH) questionnaires. Data analysis was carried out univariately and bivariately using the Chi-Square test. The results shows that the majority of respondents have a moderate level of mental health literacy (56.6%) and a positive attitude toward seeking professional psychological help (57.8%). The bivariate analysis results show a p-value of 0.020, indicating a meaningful relationship between mental health literacy and attitudes toward seeking professional psychological help.There is a significant relationship between mental health literacy and the attitude toward seeking professional psychological help among adolescents. The higher the level of mental health literacy, the more positive the attitude in seeking professional psychological help.